2020
DOI: 10.1016/j.toxcx.2020.100058
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of zearalenone and α-zearalenol in swine liver and reproductive tissues using GC-MS

Abstract: The mycotoxin zearalenone (ZEN) is a common contaminant of swine feed which has been related to a wide range of reproductive anomalies in swine, such as pelvic organ prolapse, anestrous, and pseudopregnancy. New information is needed to understand how ZEN and related metabolites accumulate in swine reproductive tissues. We conducted a feeding study to track ZEN and the metabolite α-zearalenol (α-ZEL) in swine liver and reproductive tissues. Thirty pubertal gilts were randomly assigned one of three treatments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Fusarium , a kind of fungi, is widely distributed in nature and is common in North America, Asia and Europe with mild climates [ 1 ]. Mycotoxins are produced by Fusarium , which is a major and serious threat to animal and human health, as well as livestock production [ 2 , 3 , 4 ]. In terms of animal health and productivity, the most important mycotoxins were trichothecenes, zearalenone (ZEA), deoxynivalenol and fumonisins B 1 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium , a kind of fungi, is widely distributed in nature and is common in North America, Asia and Europe with mild climates [ 1 ]. Mycotoxins are produced by Fusarium , which is a major and serious threat to animal and human health, as well as livestock production [ 2 , 3 , 4 ]. In terms of animal health and productivity, the most important mycotoxins were trichothecenes, zearalenone (ZEA), deoxynivalenol and fumonisins B 1 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal tract is one of the most sensitive tissues to these mycotoxins [ 1 ]. Studies have shown that mycotoxins can damage animal intestines through impairing the reduction–oxidation reaction balance of the body, affecting the digestive tract function and causing intestinal villus atrophy and an inflammatory response in the intestinal epithelial cells of piglets [ 3 , 7 , 8 ]. Some in vitro studies have shown that food contaminated by ZEA and ZEA metabolites can affect the synthesis of porcine cytokines and the structural integrity of the intestinal epithelium [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…POP is defined as "the genesis of single or additional of the anterior wall of vagina, posterior wall of vaginal, the cervix or the peak of the vagina" [3]. A loss of regular connection and support leads to entry of the pelvic organs into the vaginal canal [4], affecting 50% of all women over 50 years of age [5]. Rarely, the pelvic organs directly cause life-threatening disease due to weakening of the pelvic support structure (muscle, fascia, and tongue), causing the uterus, bladder, rectum, and small intestine to protrude from the vagina [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods for the detection of DON. Instrumental analysis methods include high-performance liquid chromatography (HPLC) [ 8 ], Liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) [ 4 ], ultra-performance liquid chromatography (UPLC) [ 9 ], gas chromatography with mass spectrometry (GC-MS) [ 10 ], and high-performance liquid capillary electrophoresis (HPCE) [ 11 ]. HPLC is currently the most commonly used confirmative detection method for mycotoxins [ 12 ].…”
Section: Introductionmentioning
confidence: 99%